FINANCIAL FEASIBILITY ANALYSIS OF LANDRACE PIGS CROSSES FATTENING (Case Study on UD. Intan Ray in Gadungan Village, Tabanan) - I M. A. W., Perdana; Sukanata, I W.; Sumardani, N. L. G. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
A research had been carried out to analysis the management production and financial feasibility of analyzing business of fattening Landrace pigs crossbreed from November 2016 to February 2017 in the UD. Intan Ray located in Gadungan Villages, Tabanan. The research were used the primary and secondary data. The financial feasibility of the business was determined based on the results of the analysis of investment criteria, the analysis of the Pay Back Period and Break Even Point. The research showed that UD. Intan Ray has paid attention to several aspects in the pig fattening management including: the selection of piglets, cage, feed, disease prevention and handling, labour, and marketing but they aren’t yet maximal. The business has Net Present Value / NPV of Rp 149.351.115,- IRR 30,97%, Net B/C 1,61, Pay Back Period 1,37 year and Break Even Point achived on 4,82 years. The results of the analysis showed that this business are feasible when the number of maintenance pigs were more than 33 animals/year or the selling price more than Rp. 22.390/kg. Thus it can be concluded that fattening pigs of Landrace crossbreed at UD. Intan Ray wass feasible financially. Keywords: fattening pigs, financial feasibility , Landrace pigs crossbreed